2015
DOI: 10.1159/000440845
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa-Induced Motor and Dopamine Receptor Changes in <b><i>Caenorhabditis elegans</i></b> Overexpressing Human Alpha-Synuclein

Abstract: Background: Levodopa-induced dyskinesia (LID) is a disabling complication of levodopa therapy in Parkinson's disease (PD) with no effective treatments. Fluctuations in levels of levodopa constitute a key risk factor of LID. There is a pressing need for the development of a simple animal model of LID. Several genetic and toxin-based models of PD in Caenorhabditis elegans have been described, which have advanced our understanding of PD pathophysiology. We aimed to study levodopa-induced changes in a Parkinson's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 24 publications
(32 reference statements)
4
16
1
Order By: Relevance
“…Ergo, exposure to 60 mM L-DOPA recovers the motor response, before the worm can grow tolerant once again. A previous study reported hyperactivity with lack of purpose in L-DOPA-treated C. elegans (Gupta et al 2016), which was consistent with our study showing greater locomotion scores but with increasing neurodegeneration. the latter being the probable reason for the loss in prudent locomotion.…”
Section: Discussionsupporting
confidence: 93%
“…Ergo, exposure to 60 mM L-DOPA recovers the motor response, before the worm can grow tolerant once again. A previous study reported hyperactivity with lack of purpose in L-DOPA-treated C. elegans (Gupta et al 2016), which was consistent with our study showing greater locomotion scores but with increasing neurodegeneration. the latter being the probable reason for the loss in prudent locomotion.…”
Section: Discussionsupporting
confidence: 93%
“…CAT-2 (tyrosine 3-monooxygenase) catalyzes the conversion of tyrosine (Tyr) to L-DOPA. [17,25] Therefore, DA is rarely produced in the CB1112 strain with loss-of-function mutation in cat-2 through this major pathway. As shown in BSR and alcohol avoidance assay (Figure 4B and Figure S7, Supporting Information), these typical DA behaviors were completely disappeared in cat-2 mutant worms suggesting a correspondence to the function of Cat-2 in the DA metabolism pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both PD and LID are caused by dysfunctional DA signaling although PD is due to reduced DA signaling while LID is by increased and uncoordinated DA activities. Recently, it has been shown that hyperkinetic activity and altered D1 signaling underlie L-DOPA induced dyskinesia in C. elegans [ 28 ], further supporting the notion that uncontrollable DA signaling is a key pathological mechanism of LID. One important factor considering use of Drosophila model for LID is the similarity of DA signaling mechanisms in mammals and Drosophila.…”
Section: Discussionmentioning
confidence: 80%
“…Previously, there were few LID models which can be used to study underlying pathophysiological mechanisms, genetic/molecular targets initiating the development of LID, and potential pharmacological therapies [ 27 ], largely due to lack of rich genetic resources. Recently, Gupta et al [ 28 ] has been developed C. elegans LID model expressing human α-synuclein, which shows increase body bending with L-DOPA. Overall, our Drosophila genetic LID model will provide an important experimental platform to examine molecular and cellular mechanisms underlying LID, to study the role of PD causing genes in the development of LID, and to identify potential targets to slow and/or reverse LID pathology.…”
Section: Discussionmentioning
confidence: 99%